Sustainable recycling in an imperfect production system with acceptance quality level dependent development cost and demand. (April 2020) - Khara, Barun; Dey, Jayanta Kumar; Mondal, Shyamal Kumar
Highlights: An integrated closed-loop supply chain production inventory model has been developed. The remanufacturing and manufacturing processes have been considered simultaneously to overcome the lost sale situation. Acceptance quality level dependent development cost and demand have been constructed. Abstract: This paper considers a closed-loop supply chain production inventory model consisting of a virgin raw material supplier, a manufacturer, a retailer and a collector who collects the used product from consumers at a return rate depending on acceptance quality level of the used product. Here, two types of products are produced: manufactured product using virgin raw materials and remanufactured product using used manufactured product. So, to make the model more realistic, here, the manufacturer incorporates two separate remanufacturing and manufacturing infrastructures to process simultaneously to produce remanufactured and manufactured items due to overcome the lost sale situation arisen in several published model. Again, since the quality of a product from a remanufacturing process mostly depends upon the acceptance quality level of the used product, hence an acceptance quality level dependent development cost has been considered in remanufacturing process. Also, both demand of the remanufactured products and procurement cost of the used products from collector to manufacturer have been considered as a function of acceptance quality level of returned items. Moreover, remanufacturing and manufacturing processes produce some defective items which are reworked within the same cycle. With these considerations, a mathematical model has been developed (i) to find out optimum acceptance quality level of the used manufactured product for recycling, (ii) to overcome the lost sale situation due to unsatisfied demand of remanufactured (manufactured) product at the time of manufacturing (remanufacturing) process and (iii) to obtain optimum number of deliveries from supplier to manufacturer, from manufacturer to retailer and from collector to manufacturer that maximize total integrated profit. To get the optimum solutions of the proposed model, sequential and global optimizations methods have been used. Finally, the model has been analyzed numerically to study the feasibility taking several examples.